Implementing the information literacy framework : a practical guide for librarians - Harmeyer, Dave, 1956-; Baskin, Janice J., 1951- (Lanham Rowman & Littlefield, 2018)
"This book and its website address the implementation of the The Framework of Information Literacy in Higher Education. It gives the tools and strategies to implement Framework-based information literacy experiences for students and faculty, creating a campus culture that understands, and integrates, information literacy in its educational mission" --
At the crossroads: reframing information literacy instruction -- From standards to framework : the difference and why it matters -- Pre-framework ideas to do this year -- The culture in the classroom -- Joining the information literacy conversation in education -- Tips for creating a framework campus culture -- Practical framework inroads -- Teaching information literacy : first three frames of the framework -- Teaching information literacy : last three frames of the framework -- Moving forward in creating framework-based information literacy instruction.
Includes bibliographical references and index.
Keywords: Information literacy -- Study and teaching (Higher); Academic libraries -- Relations with faculty and curriculum